2021
DOI: 10.1111/jocd.14137
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the oral supplementation of L‐Cystine associated with reduced L‐Glutathione‐GSH on human skin pigmentation: a randomized, double‐blinded, benchmark‐ and placebo‐controlled clinical trial

Abstract: Background: Glutathione has become a potential skin-lightening ingredient after the discovery of its anti-melanogenic properties. Various mechanisms of action have been considered to explain this property, one of them being the skewing of the melanin synthesis pathway toward the production of lighter pheomelanin instead of darker eumelanin, consequently producing a lightening effect. Aims:To evaluate the skin lightening and anti-dark spot effects of oral supplementation with L-Cystine associated with L-Glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Reduced GSH (M w ≈ 307.33), a highly active antioxidant, is widely distributed in the skin tissue fluid with the concentration of 2~20 μM 49 , 50 . GSH could reduce EGF by opening the disulfide bond, rendering it inactive 51 , 52 .…”
Section: Resultsmentioning
confidence: 99%
“…Reduced GSH (M w ≈ 307.33), a highly active antioxidant, is widely distributed in the skin tissue fluid with the concentration of 2~20 μM 49 , 50 . GSH could reduce EGF by opening the disulfide bond, rendering it inactive 51 , 52 .…”
Section: Resultsmentioning
confidence: 99%
“…Wahab et al 128 in a double‐blind randomized controlled study involving 46 subjects found glutathione an effective skin‐lightening agent and a combination of topical and oral glutathione was superior than either route used alone. Another randomized, double‐blind, placebo‐controlled clinical trial comprising 124 Asian females demonstrated significant skin‐lightening and reduction in size of facial pigmentation after oral supplementation with combination of l‐cystine and l‐glutathione 129 . While benefits of skin lightening with 500 mg/d orally administered glutathione given for 4 weeks were limited to certain age groups and body areas in 60 healthy Asian subjects, no significant improvement occurred in 16 patients receiving glutathione and any improvement seen in two separate randomized controlled trials was short lasting 130–132 …”
Section: Miscellaneous Therapiesmentioning
confidence: 99%
“…The results of its efficacy to treat melasma remain variable 128–131 . Wahab et al 128 in a double‐blind randomized controlled study involving 46 subjects found glutathione an effective skin‐lightening agent and a combination of topical and oral glutathione was superior than either route used alone.…”
Section: Miscellaneous Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress leads to high levels of haemolymph dopamine, an intermediate compound in the melanization pathway (Box 1). The antioxidant glutathione (GSH), can influence pigmentation by shifting production from eumelanin to pheomelanin (Box 1), which can change the colour and darkness of skin (Duperray et al, 2022).…”
Section: Metals and Micronutrientsmentioning
confidence: 99%